Evaluation of the Atibaia River water quality using Lecane bulla as a test organism - Castanha, Rodrigo Fernandes; Angelis, Dejanira De Franceschi De [UNESP]; Butturi-gomes, Davi [UNESP]; Angelis, Derlene Attili De (Instituto Biológico, 2015)
In view of the diversity of environments found in the Brazilian territory, it is understandable that the use of native species can provide more relevant information for ecotoxicological studies. The purpose of this work was to evaluate the quality of water samples from the Atibaia River in an area that is under the influence of petroleum refinery using a native test-organism and submitting the data to PCA statistical analysis. Therefore, acute toxicity assays with Lecane bulla (Rotifera) were performed in four locations of the river, as well as physical-chemical analyses. Sampling was drawn in the dry and rainy seasons. The bioassays were static and lasted 48 hours; dead organisms were quantified at the end of the tests. Toxicological differences among the samples/per location and control were compared by means of the Analysis of Variance. Physical-chemical and mortality variables were simultaneously analyzed by multivariate analysis of the principal components and the Pearson correlation coefficient. Water samples from the exit of the refinery stabilization pond (location S.1) were toxic to L. bulla in both seasons, with significant differences in relation to the control and between the seasons. The statistical treatment of data showed that mortality was strong and positively correlated with total hardness, chlorides and EC, which together with pH presented higher values in location S.1, in the dry and in the rainy seasons. Due to its sensibility to the quality of the Atibaia river water samples, the potential use of L. bulla for ecotoxicological studies as an alternative test organism could be demonstrated.

Em virtude da diversidade de ambientes encontrada no território nacional, o uso de espécies nativas em estudos toxicológicos constitui assunto de extrema relevância. Este trabalho objetivou avaliar a qualidade das águas do rio Atibaia, em uma região sob influência de uma refinaria de petróleo utilizando-se um organismo-teste nativo, e aplicando-se o método estatístico multivariado análise de componentes principais (PCA). Ensaios de toxicidade aguda com o rotífero Lecane bulla (Rotifera) e análises físico-químicas foram realizados com amostras obtidas em quatro diferentes pontos do rio em questão. As amostragens ocorreram nas estações seca e chuvosa. Os bioensaios foram estáticos e duraram 48 horas; organismos mortos foram quantificados no final dos testes. Diferenças toxicológicas entre as amostras de cada ponto e o controle foram comparadas por análise de variância. As variáveis físico-químicas e a mortalidade foram simultaneamente submetidas à análise multivariada dos componentes principais e pela correlação de Pearson. Amostras de água retiradas da saída da lagoa de estabilização (ponto S.1) foram tóxicas ao organismo L. bulla nas duas estações, com diferenças significativas em relação ao controle e entre as estações. O tratamento estatístico dos dados demonstrou que a mortalidade correlacionou-se forte e positivamente com parâmetros como dureza total, cloretos e EC, e, com o pH, apresentou valores maiores no ponto S.1 em ambas as estações. A sensibilidade apresentada pela espécie L. bulla em relação à qualidade das amostras da água do rio Atibaia indicou que este organismo apresenta potencial de uso para estudos de ecotoxicologia, podendo ser futuramente empregado como organismo-teste alternativo.
Avaliação da qualidade das águas do Rio Atibaia usando Lecane bulla como organismo teste
Keywords: Multivariate analysis; PCA; Bioassays; Acute toxicity; Rotifer; Análise multivariada; PCA; Bioensaios; Toxicidade aguda; Rotífera